Immunization coverage against the hepatitis B virus in children from chronic carrier mothers. Huanta, Ayacucho, 2014-2018 - Crispin-Huamani, Luis (2019)
Introduction. In the framework of the plan for the elimination of infection with hepatitis B virus (HBV), it's necessary to know the immunization coverage in the children of carrier mothers. Objective. To determinethe level of immunization coverage in children born to mothers with HBV infection at the Hospital de Huanta, Ayacucho, between 2014 and 2018. Methods. A descriptive observational study was carried out. The population included children born to mothers with HBV infection. Secondary information sources of immunization record against HBV were used. Results There were 90 mothers carrying the HBV infection whose children were born at the study site. The total immunization coverage against HBV was 64,47%, the coverage of the birth dose of the vaccine was 100% and the coverage of application of immunoglobulin antihepaitis B of 77,78%. Conclusions. The total immunization coverage against HBV is below what was expected according to WHO recommendations.